Rare Adult Subtype of Rhabdomyosarcoma, a Common Childhood Soft Tissue Carcinoma - Manasa Dondapati MS3; Jonathan Vincent M. Reyes MD; Saad Ahmad DO; Aaron S. Stern MD; Joseph J. Lieber MD (SAGE Publishing, 2021)
Rhabdomyosarcoma is a malignant soft tissue sarcoma of primitive mesenchymal cells, showing varying degrees of striated skeletal muscle cell differentiation. It is a very common cancer of childhood and adolescence, but rarely seen in the adult population. Here, we present a case of a 33-year-old male presented with a poorly differentiated desmin positive alveolar rhabdomyosarcoma in the left arm. The prognosis of alveolar rhabdomyosarcoma in adults is very poor, frequently detected at advanced stages or with metastases. The alveolar subtype in particular has been found to have a more aggressive course with a high rate of metastasis. Recent studies have shown that using pediatric treatment guidelines resulted in better survival outcomes and local control, but the survival rates are still below that of the pediatric population. Newer studies are looking into using specific molecular markers for more targeted therapy in hopes of further improving survival rates in the adult population.